Broadcasting & communications - Fox, Linda (New York : Arco Pub., 1978)
Describes the inner workings of the equipment used in telecommunications and broadcasting.
This material previously appeared in the publication, How it works.
Includes index.
Keywords: Telecommunication -- Juvenile literature; Broadcasting -- Juvenile literature